Applying anthropometry in sport: From talent identification to elite sport - Esparza-Ros, F.; Vaquero-Cristóbal, R. (Anthropometry, 2025)
Predicting sports performance requires a multifactorial approach. However, anthropometry has emerged as a key tool for assessing and predicting performance in various sports disciplines, allowing for talent identification and training optimisation. This chapter delves into the relationship between sports performance and body composition, especially referring to the fat and muscular component, or other anthropometric variables such as stretch stature, body mass, relative sitting height, relative length of the upper limb, brachial index, and acromial-iliac index. In addition, anthropometry is a key resource to consider in the process of detection and monitoring of sports talents. This chapter explains the need to approach the identification of sports talents from the perspective of anthropometric variables, with the consideration of biological maturation due to its influence on performance at growth ages being crucial. This chapter delves into the various methods to assess biological maturation.